Disputing parenthood at the civil registry in Côte d'Ivoire in the 1960s - (:unkn) unknown (My University, 2021)
This contribution draws on legal cases to highlight the role of individual participation in the civil registration process at the end of the colonial period in Côte d'Ivoire. Mothers and family members used civil registration to assert their rights to the newly gained privileges of citizenship. The civil registration imposed in 1950 in French West Africa was not driven by a logic of surveillance and control as it had been in previous decades. The rise of a social state in the development era had created a need for applicants, and civil registration became a means to access benefits. The contribution reveals how private agendas such as claims of parenthood and conjugal rights got enmeshed in the making of the state and in the identification bureaucracy.
Keywords: African Research